Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pengguna Jasa Penyeberangan Rute Waipirit-Hunimua - Nizwar, Nizwar; Tousalwa, Carla; Waelauruw, Anthoneta Telsy (Jurnal Administrasi Terapan, 2024)
This study aims to determine the effect of service quality on passenger satisfaction using the ferry service route Waipirit- Hunimua. This research was conducted against the background of the importance of maintaining consumer loyalty by providing satisfaction to them through quality services. This research is quantitative research with simple linear regression technique. Collecting data using a questionnaire distributed to 100 respondents. Data processing is carried out with the help of SPSS 22 software. From the research that has been done, it can be concluded that there is a positive influence of service quality on passenger satisfaction using the ferry service for route Waipirit-Hunimua. The contribution of service quality to passenger satisfaction is 84.5% while the remaining 15.5% is influenced by other variables not examined in this study. The regression equation obtained is consumer satisfaction = 6.434+0.204 (Service Quality) Keywords : Influence, Service Quality, Passenger Satisfaction